2023
DOI: 10.1093/neuonc/noad045
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive outcomes after multimodal treatment in adult glioma patients: A meta-analysis

Abstract: Purpose Cognitive functioning is increasingly assessed as a secondary outcome in neuro-oncological trials. However, which cognitive domains or tests to assess, remains debatable. In this meta-analysis, we aimed to elucidate the longer-term test-specific cognitive outcomes in adult glioma patients. Methods A systematic search yielded 7098 articles for screening. To investigate cognitive changes in glioma patients and differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…As demonstrated in recent randomized trials and the present study, glioma patients are at high risk of developing cognitive decline during their course of disease. 3 Although the relationship between brain damage and neurological function is generally well established for the eloquent primary cortical areas and their associated fiber tracts, 35 the underlying causes of cognitive deterioration in brain tumor patients remain poorly understood. 36–38 Nevertheless, initial studies in glioma patients suggested that evaluating brain networks may help further elucidate the cognitive decline of various domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated in recent randomized trials and the present study, glioma patients are at high risk of developing cognitive decline during their course of disease. 3 Although the relationship between brain damage and neurological function is generally well established for the eloquent primary cortical areas and their associated fiber tracts, 35 the underlying causes of cognitive deterioration in brain tumor patients remain poorly understood. 36–38 Nevertheless, initial studies in glioma patients suggested that evaluating brain networks may help further elucidate the cognitive decline of various domains.…”
Section: Discussionmentioning
confidence: 99%
“… 1 The prognosis of patients with gliomas mainly depends on molecular and histomorphologic tumor features that determine the growth rate and pattern of invasion into the normal brain tissue. 2 Apart from a reduced survival time, glioma patients frequently experience disturbances of cognitive function 3 that are potentially related to the structural damage imposed on the brain by the tumor itself or therapeutic interventions. Compared to other neurological disorders, such as stroke, multiple sclerosis, or dementia, the pattern of brain lesions in glioma patients is more heterogeneous, as it may comprise brain infiltration by residual or recurrent tumor growth, disruption of the blood-brain barrier, neurosurgical resection of cortical or subcortical brain tissue, or radiation- or chemotherapy-induced damage of white matter.…”
mentioning
confidence: 99%
“…Neurological deficits impact 44–50% of patients with glioma before surgery ( 52 , 68 ) and are more than three times more frequent in patients with diffuse glioma than in age- and sex-matched people from the general population ( 68 ), with cognitive performance often declining over time ( 69 ). These deficits have been identified as reducing HRQoL, with new-onset deficits associated with a reduction of 0.17 in EQ-5D 3L index values relative to no deficit in diffuse lower-grade glioma ( 46 ).…”
Section: Burdenmentioning
confidence: 99%
“…The overall survival of these patients has considerably evolved over the last two decades, mainly due to the systematization of extensive and early surgical approaches in comparison to "wait and watch" attitudes [27]. However, the natural history of the disease and the cumulative adverse effects of oncological therapies may have a drastic impact on patients' QOL, including individual professional perspectives [28], wellbeing [29], and cognitive functioning, whether at early stages of the disease (and even before the first therapeutical steps [30]) or at the later stages of the oncological management [31]. Consequently, preserving QOL in the long run remains the main objective of the oncological strategies.…”
Section: Functional Goalsmentioning
confidence: 99%